QIRAAT AL-QUR’AN DAN PROBLEMATIKANYA - Zainuddin Hamkah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
Reading the Qur'an (Qiraat al-Qur'an) with seven dialects is intended to provide convenience and flexibility for readers. It's just that there are differences in the interpretation of scholars about the meaning of the Prophet's hadith which means